Experiences and obstacles of psychologists in the accompaniment of end-of-life processes - Fernández-Alcántara, Manuel; García-Caro, MªPaz; Pérez-Marfil, Mª Nieves; Cruz-Quintana, Francisco (Anales de Psicología / Annals of Psychology, 2012)
Psychologists are responsible for the emotional care to patients who are in end-of-life processes. Little is known about the experiences, the obstacles and problems they face when addressing such complex situations, so the main objective of this research is to understand and explore what they are. A qualitative phenomenological design was performed, using semi structured interviews, which were analyzed with the software Atlas.ti following an open coding. The sample consisted of 15 psychologists who perform their work in palliative care, other hospital units (oncology, mental health, emergency and early intervention) or privately involved in the province of Granada (Spain). The results show how psychologists contact with patients in end-of-life processes, as well as the variety of both positive and negative experiences in their speech. It is shown the existence of various obstacles that have to do with the timing of intervention, characteristics of the patient or family, with the emotions of the psychologist, as well as the health organization. This study shows how the feelings of the psychologists can influence their intervention, which raises the need for a specific training where they can learn different strategies to overcome the obstacles posed by intervention at the end-of-life.